2018
DOI: 10.1007/s40687-018-0150-4
|View full text |Cite
|
Sign up to set email alerts
|

K3 string theory, lattices and moonshine

Abstract: In this paper, we address the following two closely related questions. First, we complete the classification of finite symmetry groups of type IIA string theory on K 3 × R 6 , where Niemeier lattices play an important role. This extends earlier results by including points in the moduli space with enhanced gauge symmetries in spacetime, or, equivalently, where the world-sheet CFT becomes singular. After classifying the symmetries as abstract groups, we study how they act on the BPS states of the theory. In part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
70
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 22 publications
(73 citation statements)
references
References 97 publications
(407 reference statements)
3
70
0
Order By: Relevance
“…In some cases, the possible twining genera φ g for a given Frame shape are Jacobi forms with a non-trivial complex-valued multiplier. This happens if and only if the length of the shortest cycle in the Frame shape is > 2, see [10]. In this case, there are always at least two different twining genera at n = 1, with complex conjugate multipliers [10].…”
Section: )mentioning
confidence: 99%
See 2 more Smart Citations
“…In some cases, the possible twining genera φ g for a given Frame shape are Jacobi forms with a non-trivial complex-valued multiplier. This happens if and only if the length of the shortest cycle in the Frame shape is > 2, see [10]. In this case, there are always at least two different twining genera at n = 1, with complex conjugate multipliers [10].…”
Section: )mentioning
confidence: 99%
“…This happens if and only if the length of the shortest cycle in the Frame shape is > 2, see [10]. In this case, there are always at least two different twining genera at n = 1, with complex conjugate multipliers [10]. For the Frame shapes 6 4 and 4 2 8 2 , where there are more than two candidate twining genera, we separate by a horizontal line the twining genera with different multipliers.…”
Section: )mentioning
confidence: 99%
See 1 more Smart Citation
“…Since the elliptic genus only counts BPS states of the theory, one might have hoped that the BPS states have M 24 as symmetry group, but the full spectrum has a different symmetry group. By calculating explicit twined elliptic genera [18,19] one finds that there are more twined elliptic genera for K3 spaces than conjugacy classes of M 24 . The symmetry groups of the K3 manifold at different points in moduli space have found a beautiful string theory explanation in [20], where the authors study type IIA string theory on K3×T 3 .…”
Section: Jhep02(2018)129mentioning
confidence: 99%
“…So one should ask which group is relevant for the elliptic genus which counts a subset of states independently of where we are in moduli space. These questions are not easily answered but it has been shown that twined elliptic genera for K3 manifolds give all the McKay-Thompson series of Mathieu moonshine plus several extra twined elliptic genera that one would not have expected based on Mathieu moonshine alone [18]. At the same time the idea of symmetry surfing has been pursued, in which one tries to find an explicit M 24 symmetry by combining the symmetry groups at different points in K3 moduli space [13][14][15][16].…”
Section: Jhep02(2018)129 6 Conclusionmentioning
confidence: 99%